PERBEDAAN TINGKAT KONSUMSI ENERGI, KEBIASAAN OLAHRAGA DAN STATUS GIZI BERDASARKAN JENIS EKSTRAKURIKULER PADA SISWA DI SMAN 1 SUKAWATI - Ida Ayu Wedastri Pradnyani; I Wayan Ambartana; Ni Made Dewantari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
Students participate in a lot of activities at school, so to support the implementation of school and extracurricular activities it is necessary to have a good nutritional status for students, energy consumption as needed, and maintain nutritional status by doing sports. The purpose of this study was to determine differences in the level of energy consumption, exercise habits and nutritional status based on extracuriculler type of students in Senior High School No 1 Sukawati. This type of research is observational with a cross-sectional design. The research site at State Senior High School No 1 Sukawati with a large sample was 75 people. Sampling was done using the Purposive Sampling method. Energy consumption level data is collected with 2x24 hour recall. Data on exercise habits were collected using a questionnaire. Data nutritional status were collected by anthropometric measurements. Analysis of differences with the Independent t-test. The results showed that the level energy consumption of basketball group and group of Paskibra that is there was no significant difference in the level of energy consumption of students. Then the sports habits of  basketball group and group of Paskibra there are no significant differences in students's sports habits. While the nutritional status of basketball group and group of Paskibra there are no significant differences in student’s nutritional status.Keywords: Energy consumption level, nutritional status,exercise.